Long noncoding RNAs transcribed downstream of the human β-globin locus regulate β-globin gene expression. (8th December 2021) - Higashi, Miki; Ikehara, Tsuyoshi; Nakagawa, Takeya; Yoneda, Mitsuhiro; Hattori, Naoko; Ikeda, Masaaki; Ito, Takashi
Abstract: The five β-like globin genes (ε, Gγ, Aγ, δ and β) at the human β-globin gene locus are known to be expressed at specific developmental stages, although details of the underlying mechanism remain to be uncovered. Here we used an in vitro transcription assay to clarify the mechanisms that control this gene expression. We first tested nuclear RNA from HeLa cells using RT-qPCR and discovered a long noncoding RNAs (lncRNAs) within a 5.2-kb region beginning 4.4 kb downstream of the β-globin gene coding region. We investigated nuclear RNA from K562 cells using a primer-extension assay and determined the transcription start sites (TSSs) of these lncRNAs. To clarify their functional role, we performed knockdown (KD) of these lncRNAs in K562 cells. Hydroxyurea (HU), which induces differentiation of K562 cells, increased haemoglobin peptide production, and the effect was enhanced by KD of these lncRNAs, which also enhanced upregulation of the γ-globin expression induced by HU. To confirm these results, we performed an in vitro transcription assay. Noncoding single-stranded RNAs inhibited β-globin expression, which was upregulated by GATA1. Furthermore, lncRNAs interacted with GATA1 without sequence specificity and inhibited its binding to its target DNA response element in vitro . Our results suggest that lncRNAs downstream of the β-globin gene locus are key factors regulating globin gene expression. Graphical Abstract: